Gathering Alumni Information from Web using Machine Learning - Sudalaimuthu T, S. Balasubramani, M. Subramaniyan3, P. Ganesan, S. Vinothkumar (International Journal of Advanced Science and Technology, 2020)
Alumni network is the most powerful strength for any academic institution. The Higher Education institution (HEI) also requires to collect the alumni feedback  to measure the programme outcome and the markets needs. The HEIs use many forms to collect the information from alumni, unfortunately maintaining alumni database and collect the information from alumni is not so easy job for HEIs. Many social networks available to associate with alumni of the institution. The proposed machine learning based web applications is designed to identify the alumni and collect the information as required by the institution. The proposed ML based web application is tested in with the traditional applications for a small group. The results are analyzed and discussed. It is found that the proposed applications were able to perform 17.65% more than traditional applications.Keywords–Machine Learning, Alumni Networks, Higher Education Institution, Search Engine, Social media